Clinical Feasibility of 3-Dimensional Magnetic Resonance Cholangiopancreatography Using Compressed Sensing: Comparison of Image Quality and Diagnostic Performance. Issue 10 (October 2017) - Yoon, Jeong Hee; Lee, Sang Min; Kang, Hyo-Jin; Weiland, Elisabeth; Raithel, Esther; Son, Yohan; Kiefer, Berthold; Lee, Jeong Min
Abstract : Objective: The aim of this study was to evaluate the clinical feasibility of fast 3-dimensional (3D) magnetic resonance cholangiopancreatography (MRCP) using compressed sensing (CS) in comparison with conventional navigator-triggered 3D-MRCP. Materials and Methods: This retrospective study was approved by our institutional review board, and the requirement of informed consent was waived. A total of 84 patients (male-to-female ratio, 41:43; mean age, 47.3 ± 18.8 years) who underwent conventional 3D navigator-triggered T2-weighted MRCP using sampling perfection with application optimized contrasts (SPACE) and fast 3D MRCP using SPACE with high undersampling combined with CS reconstruction (CS SPACE; CS-MRCP) on a 3 T scanner were included. Among them, 28 patients additionally underwent 3D breath-hold CS-MRCP (BH-CS-MRCP) with 5.7% k-space sampling. Three board-certified radiologists then independently reviewed the examinations for bile duct and pancreatic duct visualization and overall image quality on a 5-point scale, and image sharpness and background suppression on a 4-point scale, with the higher score indicating better image quality. In addition, diagnostic performance for the detection of anatomic variation and diseases of the bile duct, and pancreatic disease were assessed on a per-patient basis in the subgroup of 28 patients who underwent conventional MRCP, CS-MRCP, and BH-CS-MRCP in the same manner. Results: Mean acquisition times of conventional MRCP, CS-MRCP, and BH-CS-MRCP were 7 minutes (419.7 seconds), 3 minutes 47 seconds (227.0 seconds), and 16 seconds, respectively ( P < 0.0001, in all comparisons). In all patients, CS-MRCP showed better image sharpness (3.54 ± 0.60 vs 3.37 ± 0.75, P = 0.04) and visualization of the common bile duct (4.55 ± 0.60 vs 4.39 ± 0.78, P = 0.034) and pancreatic duct (3.47 ± 1.22 vs 3.26 ± 1.32, P = 0.025), but lower background suppression (3.00 ± 0.54 vs 3.37 ± 0.58, P < 0.001) than conventional MRCP. Overall image quality was not significantly different between the 2 examinations (3.51 ± 0.95 vs 3.47 ± 1.09, P = 0.75). The number of indeterminate MRCP examinations for the anatomic variation and disease of the bile duct significantly decreased on CS-MRCP, from 16.7%–22.6% to 9.5%–11.9% and 8.4%–15.6% to 3.6%–8.4% in all readers ( P = 0.003–0.03). In the 28 patients who underwent BH-CS-MRCP, better image quality was demonstrated than with conventional MRCP and CS-MRCP (4.10 ± 0.84 vs 3.44 ± 1.21 vs 3.50 ± 1.11, respectively, P = 0.002, 0.001). Sensitivities for detecting bile duct disease was 88.9% to 100% on both BH-CS-MRCP and conventional MRCP ( P > 0.05), and for detecting pancreatic disease was 66.7% to 83.3% on BH-CS-MRCP and 50.0% to 72.2% on conventional MRCP ( P = 0.002 in reader 1, 0.06–0.47 in readers 2–3). Conclusions: Compressed sensing MRCP using incoherent undersampling combined with CS reconstruction provided comparable image quality to conventional MRCP while reducing the acquisition time to within a single breath-hold (16 seconds). Abstract : Supplemental digital content is available in the text.